Curcumin enhances the anti-cancer efficacy of paclitaxel in ovarian cancer by regulating the miR-9-5p/BRCA1 axis - Liu, Yuwan; Shen, Zhangjin; Zhu, Tingjia; Lu, Weiguo; Fu, Yunfeng (Frontiers in Pharmacology, 2023)
Patients with late-stage ovarian cancer continue to have a very poor prognosis. It is urgent for us to develop more effective novel therapies which improve overall survival and overcome drug resistance. Several studies established that curcumin (Cur) synergistically enhances the therapeutic effects of multiple chemotherapeutic agents, but the potential involvement of Cur in ovarian cancer is largely unknown. Here, we reported that the Cur and paclitaxel (PTX) combination synergistically inhibited proliferation and promoted apoptosis in ovarian cancer cells. Further analysis revealed that miR-9-5p and BRCA1 played essential roles in driving the synergy of Cur and PTX combination. Cur and PTX combination resulted in a reduction of miR-9-5p expression, and an increase in the BRCA1 levels. miR-9-5p overexpression or BRCA1 knockdown counteracted the synergy between Cur and PTX on cellular proliferation and apoptosis. Rescue experiments demonstrated that Cur and PTX combination exerted synergistic anti-cancer effect in ovarian cancer by regulating miR-9-5p/BRCA1 axis. Meanwhile, in vivo experiments revealed that Cur and PTX combination dramatically suppressed the growth of transplanted tumors, while miR-9-5p mimics eliminated the growth inhibition of xenografts induced by the combined treatment. Our findings provide strong evidence for clinical investigation of Cur and PTX combination as a novel strategy for patients with ovarian cancer and identify miR-9-5p and BRCA1 as key targets regulating sensitivity to this therapy.